Improvement in Stress, General Self-Efficacy, and Health Related Quality of Life following Patient Education for Patients with Neuroendocrine Tumors: A Pilot Study - Trude Haugland; Marijke Veenstra; Morten H. Vatn; Astrid K. Wahl (Hindawi Limited, 2013)
The purpose of the study was to evaluate changes in general self-efficacy, health related quality of life (HRQoL), and stress among patients with neuroendocrine tumors (NET) following a multidisciplinary educational intervention. Forty-one patients were enrolled in this exploratory pilot study. A total of 37 patients completed the full 26-week intervention based on the principles of self-efficacy. General self-efficacy was measured by the General Self-Efficacy Scale, HRQoL was measured with the SF-36, and stress was measured with the Impact of Event Scale. Mixed effect models were used to evaluate changes in general self-efficacy, mental and physical components of HRQoL, and stress adjusting for demographic and clinical variables. Results showed significant improvements in patients' general self-efficacy (β = 0.71; P<0.05), physical component scores of HRQoL (β = 3.09; P<0.01), and stress (β=-2.10, P=0.008). Findings suggest that patients with NET have the capacity to improve their ability to cope with their disease, problem-solve, improve their physical status, and reduce their stress following an educational intervention based on the principles of self-efficacy. These preliminary data provide a basis for future randomized controlled trials to test interventions to improve HRQoL for patients with NET.